PERAN PENDIDIKAN KEPRIBADIAN DALAM MENDIDIK GENERASI MUDA DI SEKOLAH KATOLIK Studi Kasus di SMP Pangudi Luhur Sedayu Yogyakarta - Fransiskus David Ludiranto (P3TK, Sanata Dharma University, 2013)
Education is one of human efforts to be a complete human. Education aims to teach young people to become homo that human, cultured human that realizes his true personality as the image of God. Therefore, education is often viewed as a part of Gods salvation. Education is a Christian journey to the fullness of human life to reach God, source and purpose of all things. Education is an appropriate way to spread Good News brought by Jesus Christ to all people. The main purpose is to educate young people to the passionate belief to Jesus Christ, the Human Salvatore because everyone who believes in him will not perish but have eternal life (John 3:16).